2022
DOI: 10.1111/oik.09549
|View full text |Cite
|
Sign up to set email alerts
|

Insularity and early domestication: anthropogenic ecosystems as habitat islands

Abstract: Over the past decade research into early domestication has been transformed by the genomics revolution and increased archaeological investigation. Despite clarification of the timing, locations and genetic processes, most scholars still envision evolutionary responses to human innovations, such as sickle harvesting, tilling, selection for docility or directed breeding. Stepping away from anthropocentric models, evolutionary parallels in the wild can provide case studies for understanding what ecological pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 127 publications
(173 reference statements)
0
6
0
Order By: Relevance
“…We further infer that: (1) when hand-reared, socialized, human-selected wolf pups reached sexual maturity they often would have reverted to the wild to breed, although some could have mated in captivity; (2) the dispersing socialized wolves commonly formed mated pairs with each other, but sometimes with wild Pleistocene wolves; the former would have most commonly established their territory in a liminal zone situated between human settlement sites (anthropogenic habitat “islands”; cf. Spengler, 2022 ) and the environment inhabited by strictly wild-living wolves, which had a natural fear of humans and actively avoided them; (3) consequently, the socialized canids often denned and whelped in the liminal zone close to human camp sites and hence each new generation of wild-born pups humans took from dens located close to their camps would include some (or many) of the offspring of human-selected canids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We further infer that: (1) when hand-reared, socialized, human-selected wolf pups reached sexual maturity they often would have reverted to the wild to breed, although some could have mated in captivity; (2) the dispersing socialized wolves commonly formed mated pairs with each other, but sometimes with wild Pleistocene wolves; the former would have most commonly established their territory in a liminal zone situated between human settlement sites (anthropogenic habitat “islands”; cf. Spengler, 2022 ) and the environment inhabited by strictly wild-living wolves, which had a natural fear of humans and actively avoided them; (3) consequently, the socialized canids often denned and whelped in the liminal zone close to human camp sites and hence each new generation of wild-born pups humans took from dens located close to their camps would include some (or many) of the offspring of human-selected canids.…”
Section: Discussionmentioning
confidence: 99%
“…Probably, humans choose for a specific segment of the wild wolf population ( cf. Spengler, 2022 ). Indeed, recent studies have shown that human-directed attachment behaviors likely existed as standing variation within Pleistocene wolf populations ( Hansen Wheat et al, 2022 ).…”
Section: The Human-initiated Model Of Wolf Domesticationmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative hypothesis is that the wild progenitors of crops were physiologically distinct. Indeed, crop domestication may have already started with distinctive wild species, as proto-farmers may have consciously or unconsciously selected for cultivation wild species with particular traits [9][10][11][12] . However, the relative importance of 'early human selection' vs. 'evolution under cultivation' to explain the fast physiological rates of crops is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Selection for desirable traits, those advantageous to cultivation, consumption, or storage, may result in a product recognizable as a land race or cultivar (Sauer, 1965;Innan and Kim, 2004;Sun et al, 2022). This traditional domestication paradigm, which implies a single propagule collection, transport, founder and habitat exposure event over a relatively short time period has been recently challenged (McKey et al, 2010;Larson et al, 2014;Spengler, 2022), especially for cereals (Allaby et al, 2021). Instead of a unified and localized process, it is argued that domestication arises from interacting metapopulations, facilitated by cultural connectivity across a landscape of diverse natural, disturbed, and cultivated habitat conditions.…”
mentioning
confidence: 99%